Pengaruh Profitabilitas dan Rasio Altman Terhadap Harga Saham ( Studi Pada Perusahaan Pertambangan Yang Go Public Di BEI ) - Wulandari, Desy; ., Carmidah; Wiratno, Adi (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2017)
This study was intended to indentify the impact of the profitability ratio and ratios in model Altman Z-Score on the prices of stocks. The study was conducted at a go public mining company registered at the Indonesia’s Stock Exchange in 2012-2015. The sample included 8 companies which were taken using purposive sampling method. The data used were the secondary data which were in the form of annual financial statements of the company and were collected using data base collection method. The data were analyzed using multiple linear regression analysis supported with SPSS 24.00 program. The result of the study showed that (1) Profitability ratio are proxied by Return On Asset (ROA) did not significantly affect the prices of stocks with sig. 0,088. (2) Altman’s ratios (Z-Score) significantly contributed to the prices of stocks with sig. 0,009.